Pelaksanaan Kawin Bajapuik Dan Uang Hilang Di Kabupaten Padang Pariaman - Razak, Rahmat Putra Syahyu; Marjon, Dahlil; Yasniwati, Yasniwati (UNES Law Review, 2023)
Marriage is an event in the life of every human being. Marriage that occurs between a man and a woman will have both physical and spiritual consequences between them, on society and also disputes with assets acquired between them both before, during and after the marriage takes place. Marriage according to customary law is a very important matter because it does not only involve the relationship between the two parties of the bride and groom, but also concerns the family relationship between the two parties. In the area of ​​West Sumatra, specialy in Padang Pariaman Regency, there is a uniqueness in the marriage system, namely the "Bajapuik" and "lost money" traditional marriages. Normally in a marriage procession, it is the man who proposes to the woman's family, but in the traditional Pariaman marriage system it is not same. In the traditional marriage procession in Padang Pariaman, the application process is carried out by the female family, the male family is only waiting for the female family to arrive. This procession occurs in the traditional Bajapuik marriage in Padang Pariaman Regency, where "Bajapuik" means "to pick up". In this study, the authors took the formulation of the problem, What are the procedures for bajapuik marriage and lost money and why is the lost money tradition still being carried out, How is the implementation of bajapuik marriage and what are the legal consequences if it is not carried out and, What are the obstacles to the collection of money and the solution to the lost marriage of bajapuik and money in Padang Pariaman. The research used is a sociological juridical approach that is analytically descriptive in nature, namely examining the reality of marriage law that applies in society. Sources of data used are primary data and secondary data. This research was conducted in 4 different places.